en - Ni Luh Anik Setiadewi; Ni Ketut Alit Ida Setianingsih; I Wayan Mulyawan (Program Magister Linguistik Universitas Udayana, 2022)
This study focuses on two aspects: (1) the translation procedures are found in English into Indonesian novel entitled Looking for Alaska; and (2) the most dominant translation procedure found in the novels entitled Looking for Alaska. The data were taken from a novel entitled Looking for Alaska and its Indonesian translation with the same title. The data collection was done by documentation method, reading and taking notes. The data were analysed by descriptive and qualitative methods. The data analysis was presented by using the informal method to describe and explain the types and translation procedures. The results suggested that (1) borrowing procedure found in the novel is 31 data, calque procedure with 10 data, literal translation procedure with 8 data, transposition procedure with 4 data, equivalence with 6 data, adaptation with 1 data; (2) the most dominant procedure used by the translator was borrowing procedure.